A QTL for rice grain yield in aerobic environments with large effects in three genetic backgrounds - Venuprasad, R.; Bool, M.E.; Quiatchon, L.; Atlin, G.N. (Springer, 2012)
A large-effect QTL associated with grain yield in aerobic environments was identified in three genetic backgrounds, Apo/2*Swarna, Apo/2*IR72, and Vandana/2*IR72, using bulk-segregant analysis (BSA). Apo and Vandana are drought-tolerant aerobic-adapted varieties, while Swarna and IR72 are important lowland rice varieties grown on millions of hectares in Asia but perform poorly in aerobic conditions. Two closely linked rice microsatellite (RM) markers, RM510 and RM19367, located on chromosome 6, were found to be associated with yield under aerobic soil conditions in all three backgrounds. The QTL linked to this marker, qDTY6.1 (DTY, grain yield under drought), was mapped to a 2.2 cM region between RM19367 and RM3805 at a peak LOD score of 32 in the Apo/2*Swarna population. The effect of qDTY6.1 was tested in a total of 20 hydrological environments over a period of five seasons and in five populations in the three genetic backgrounds. In the Apo/2*Swarna population, qDTY6.1 had a large effect on grain yield under favorable aerobic (R 2 ≤ 66%) and irrigated lowland (R 2 < 39%) conditions but not under drought stress; Apo contributed the favorable allele in all the conditions where an effect was observed. In the Apo/IR72 cross, Apo contributed the favorable allele in almost all the aerobic environments in RIL and BC1-derived populations. In the Vandana/IR72 RIL and BC1-derived populations, qDTY6.1 had a strong effect on yield in aerobic drought stress, aerobic non-stress, and irrigated lowland conditions; the Vandana allele was favorable in aerobic environments and the IR72 allele was favorable in irrigated lowland environments. We conclude that qDTY6.1 is a large-effect QTL for rice grain yield under aerobic environments and could potentially be used in molecular breeding of rice for aerobic environments